A Mindfulness-Based Intervention for Students With Psychiatric Disorders in a Special Education Curriculum: A Series of n-of-1 Trials on Internalized and Externalized Symptoms - Malboeuf-Hurtubise, Catherine; Taylor, Geneviève; Paquette, Linda; Lacourse, Eric (Frontiers in Education, 2018)
Background: Mindfulness-based interventions (MBIs) constitute a promising option to alleviate psychological symptoms in students with psychiatric disorders. Objective: This study evaluated the impact of a MBI on psychological symptoms of elementary school students with psychiatric disorders in a special education curriculum. Method: A series of n-of-1 trials with an experimental A-B-A design and 10 assessment time-points was used. Participants were two special education classrooms of elementary school students (Group A, n = 7; Group B, n = 6; ntotal = 13) and their teachers. Results: Analyses showed that, at follow-up, students from Group A reported significant decreases in inattention and a trend (p = 0.051) was observed in anxiety symptoms, whereas their teacher reported only deteriorating anxiety scores. No significant results were found in students from Group B. Conclusion: Results from this study show substantial variation between students, tested cohorts and raters of internalizing and externalizing symptoms and behaviors. Therefore, the conservative conclusion from such variation can only be that more research is needed, as no firm conclusion as to the utility of MBIs for such groups of children with special education needs can be established.